Spawning, Larval Development and Growth of Tridacna Maxima (Roding) (Bivalvia: Tridacnidae) - Alcazar, Sally; Solis, Erwinia P. (Silliman Journal, 2024)
Adult T. maxima were successfully induced to spawn in the laboratory using macerated gonad in December 1984 and January 1985. Spontaneous spawnings occurred in Pebruary and October 1985. Spawning can be induced in the morning as well as in the afternoon. Larvae were feared to the juvenile stage in larval rearing tanks and larval development monitored. A stereotyped development pattern was displayed. Less than 1% of juveniles survived from eggs. Four-month-old juveniles placed in Taceways provided with a continuous flow of unfiltered Sea water attained a mean shell length of 38.35 mm efter eight months, with an average monthly growth of 4.1mm + 0.8.